If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 + 7 = 3 Reorder the terms: -4 + 7 + 2x = 3 Combine like terms: -4 + 7 = 3 3 + 2x = 3 Add '-3' to each side of the equation. 3 + -3 + 2x = 3 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 3 + -3 2x = 3 + -3 Combine like terms: 3 + -3 = 0 2x = 0 Solving 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = 0 Simplifying x = 0
| (x-4)(x-8)=5 | | 10x^2-3x=6x-8x^2 | | 2x-9=-6 | | 2+5(10)= | | (6x^2y-4xy^2)-(-9x^2y-7xy^2)= | | 2x^2-20x-5525=0 | | 100[0.06(n+10)]= | | 2b^3-4=r^8 | | 50x-4=45x+1 | | 2y^6+9=g^1 | | 50x-1=45x+1 | | -1x-6y=5 | | C-16=18 | | B+127=52 | | -x+6y=5 | | K+6K-13=57 | | 3x*3x-2x+7=0 | | 6-3-(-10)-7+(-13)+33= | | 58(w)(w+8)=x | | (3x-5)(x-2)=0 | | 8-5x-x=14 | | (8x-5x)+(-2-8)= | | X+(3-2x)= | | -3/4+4/-7= | | 3/4+4/7= | | -3/4+-4/7= | | 3x+4y=a | | 10x^3-7x^2-12x=0 | | 3x+12=9x+36 | | 3x+12=9x+39 | | 2(3x+4)-1=9 | | 2x+13=7x+5 |